Experimental study of the effect of the wake generated by oscillating gurney flap - Marañon Di Leo, Julio (2019)
The study of the turbulent near wake of an airfoil provided with flow control devices shows the flow configuration in such conditions and the starting vortices mechanism, while, the far wake of-fers information about the general performance of the model. The objective of the present work is to study the develop of the fluid-dynamic structures found in the NACA 4412 airfoil wake, as well as the develop-ment of the same structures when flow control tech-niques are applied by means of a oscillating Gurney Flap place in the lower surface of the wing model, close to the trailing edge. Tests were performed at a given Reynolds numbers and the flow control system was set at different frequencies. In order to study the effect of the control mechanism on the wake, hot wire anemometry techniques were used. Two components of the velocity vector were measured - longitudinal and vertical - by means of a vertical array of three sensors acquiring simultaneously. The intention is to quantify the flow general configuration at the airfoil wake for different test conditions. The velocity vectors will be analyzed, together with the turbulence inten-sity and integral scales.